Scan, Pay, Eat: A Descriptive Qualitative Study of Generation Z Consumer Behavior and Street Food Vendor Response to QRIS-Based Digital Payments in Indonesia - Ade Aspandi; Nur Luthfiyani Fajrin Mima; Edi Suhardi Rahman (MASI Mandiri Edukasi, 2025)
The rapid adoption of QRIS (Quick Response Code Indonesian Standard) in Indonesia has transformed consumer payment behavior, particularly among Generation Z. However, empirical studies exploring its influence on merchant adoption in the street food sector remain limited. Previous literature has predominantly examined QRIS usage from the perspective of financial inclusion, with minimal attention to the intergenerational dynamics between digital-native consumers and small-scale vendors. This study employed a descriptive qualitative approach with thematic analysis to investigate Generation Z’s usage patterns of QRIS and merchant responses to its implementation. Primary data were collected through semi-structured interviews with ten Generation Z consumers, selected purposively based on their high frequency of QRIS use in food purchases. Two street food vendors were chosen to represent differing age groups and digital literacy levels. Findings indicate that most Generation Z participants consistently preferred QRIS over cash, citing transaction speed, ease of use, and perceived security as key factors. Several respondents stated they would avoid purchasing from vendors without QRIS availability, indicating a demand-driven influence on merchant practices. Merchant responses varied: younger, digitally literate vendors readily adopted QRIS, while older vendors encountered barriers such as limited device access and low digital literacy. The small number of merchant participants reflects the study’s focus on depth of insight rather than breadth of sampling. These results suggest that Generation Z’s payment preferences are accelerating the integration of digital payments in micro and small enterprises, though intergenerational disparities in adoption remain a challenge for broader financial technology inclusion.